Winter white : a Belles novel - Calonita, Jen (Little, Brown, 2012)
The daughters of a North Carolina senator, Isabelle and Mirabelle, who are still reeling from the knowledge that they are not cousins, but actually sisters, barely have time to process the news with cotillion season right around the corner.